(untitled) (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2026)
This study aims to analyze how the principles of Tri Hita Karana are applied in the development of students’ character through religious activities at Pura Sari, Selat Village, Buleleng. The chosen research method is qualitative descriptive with a literature review approach. The findings of this study indicate that Pura Sari, as a sacred and historical site with megalithic stone structures, plays an important role in character education based on spirituality, social values, and environmental awareness. The value of Parhyangan is applied through prayer practices that strengthen the spiritual connection with God; the value of Pawongan is reflected in ngayah activities and social interactions that enhance a sense of responsibility and empathy; and the value of Palemahan is manifested through environmental preservation activities at the temple, which foster students’ ecological awareness. The learning process occurs not only within the classroom but also through direct experiences at the temple, enabling students to internalize noble values in a holistic and relevant manner. Thus, the integration of Tri Hita Karana at Pura Sari has proven effective in shaping students’ religious, social, and ecological character comprehensively.